2020
DOI: 10.22541/au.159413291.11622259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytosterols and phytostanols and the hallmarks of cancer: a meta-analysis of pre-clinical animal models

Abstract: Background and Purpose Phytosterols and phytostanols are natural products present in vegetable oils, nuts, and seeds, or added to consumer food products and intake is inversely associated with incidence and prognosis of several cancers. Randomised cancer prevention trials in humans are unfeasible due to time and cost yet the cellular processes and signalling cascades that underpin anti-cancer effects of these phytochemicals have been explored extensively in vitro and in preclinical in vivo models. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, further studies characterising the bioactive compounds and mechanisms of action conferring health benefits are required. PSS enriched in plant-based diets lower pathogenic blood lipids (12,14,58) , are linked to reduced cancer burden and risk (16,17) and a range of other diseases. Our systematic review has collated important knowledge regarding how PSS may act as epigenetic modifiers with the following notable observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further studies characterising the bioactive compounds and mechanisms of action conferring health benefits are required. PSS enriched in plant-based diets lower pathogenic blood lipids (12,14,58) , are linked to reduced cancer burden and risk (16,17) and a range of other diseases. Our systematic review has collated important knowledge regarding how PSS may act as epigenetic modifiers with the following notable observations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for the treatment and management of hyperlipidaemia, PSS consumption is recommended by the National Lipid Association, the European Society of Cardiology and the European Atherosclerosis Society (14,15) . In addition, two meta-analyses have concluded that PSS consumption was linked to a reduced risk of developing some cancers in humans (16) and reduced cancer burden in preclinical models (17) . More broadly, PSS have also been proposed to have anti-inflammatory, anti-microbial, blood pressure lowering, anti-diabetic and anti-obesity properties (reviewed in (18) ).…”
mentioning
confidence: 99%
See 1 more Smart Citation